ESL Learners’ Perceptions of a Massive Open Online Course on Writing - Hasan , Md. Masudul; Hoon, Tan Bee (EAST WEST JOURNAL OF HUMANITIES, 2017)
Started in 2008, Massive Open Online Courses, or MOOCs, have succeeded to attract millions of learners to join MOOCs. Well-known institutions such as MIT, Stanford University and Harvard University have already adopted MOOC instructional pedagogy to offer courses on various subjects including English language courses. The present study examined a class of ESL undergraduates’ perceptions of a Massive Open Online Course on writing. Precisely, the study aimed to investigate how the participants perceived the Writing MOOC, what they liked about the course, how they learned, and what helped them learn. A case study approach involving both qualitative and quantitative data collection methods was used. The participants comprising 48 ESL undergraduates were from an intact class in a Malaysian public University. Results from the perception questionnaire and learners’ reflection essays indicated participants’ positive perceptions towards learning in the Writing MOOC. The course, the participants had followed, helped them improve their skills in writing. The empirical findings of the study have contributed to a better knowledge of the nature of learning and participation in a MOOC environment from the perspective of ESL learners.